Identity and Resistance in Further Education - Bennett, Pete; Smith, Rob (Routledge Research in Vocational Education, 2018)
In recent years, Further Education has reached a crossroads, with questions being asked about its function, aims and focus, as well as querying the role of the FE teacher, the key aspects of the curriculum and which values should inform FE pedagogy. Identity and Resistance in Further Education explores these questions and effectively conveys the sense of uncertainty that those in the field are experiencing today. Connecting Higher Education and FE practitioners and researchers, the book gathers a collection of essays covering a range of topics, including: the journey from student to teacher, critical reflective practice as a way of organising identity, values-based teacher education and policy critique. In keeping with the themes of resistance and creativity, the chapters draw on a wide range of theoretical, as well as literary, perspectives to offer answers. Problematising relationships between the teacher and the institution and the teacher and government, the book argues that the profound challenge to teachers' values and identities finds its response in a critical collegiality.This book will be of great interest to academics, researchers and postgraduate students engaged in the study of further education, educational policy and teacher education. It should also be essential reading for practitioners and policymakers. (Verlag).